1990
DOI: 10.1002/jsfa.2740520107
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the chemical composition of clonal black tea (Camellia sinensis) due to delayed withering

Abstract: A B S T R A C T The chemical composition of black teas (Camellia sinensis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Prolonged withering and temperatures above 38°C during withering have been reported to decrease the TF content and brightness of tea liquors. 20,25 The TF content and brightness varied signi®cantly throughout the manufacturing period during all the years, but the seasonal variations were less pronounced during 1996. This could be because of the inconsistent and low degree of withering during 1993 and 1994.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Prolonged withering and temperatures above 38°C during withering have been reported to decrease the TF content and brightness of tea liquors. 20,25 The TF content and brightness varied signi®cantly throughout the manufacturing period during all the years, but the seasonal variations were less pronounced during 1996. This could be because of the inconsistent and low degree of withering during 1993 and 1994.…”
Section: Resultsmentioning
confidence: 95%
“…During the rainy season the degree of withering was signi®cantly lower than in all other seasons owing to high relative humidity, which decreased evaporation of leaf moisture, thus requiring more time to reach the same degree of withering. Since delay in withering has been reported to affect the quality of black tea adversely, 20 hot air was circulated through the withering troughs during the rainy season to assist evaporation of leaf moisture. Incorporation of a hot air system helped to increase withering from below 500 mg g À1 during 1993 and 1994 to 550 mg g À1 during 1995 and 1996 in the stipulated time of 18±20 h.…”
Section: Samples Of Four Grades Ie Tippy Golden Flowerymentioning
confidence: 99%
“…Considering that higher F content has been found in BT infused in teabags than loose orthodox BT [6, 134, 150], it would appear that the introduction of the black CTC teabags to international tea markets post-1970 and the change in origin of imported tea significantly altered population exposure to F. This is evident in the differences in F levels reported in our study with those reported for BT products in NZ during the 1940s [68]. In NZ, population exposure was further exacerbated by the rapid expansion of water fluoridation in the 1960s.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical wither starts immediately leaf is detached from the plant. In practice, harvested leaf takes long durations in the field before delivery to the factories (12,22). This problem can be more complicated in the smallholder tea sector.…”
Section: Introductionmentioning
confidence: 99%
“…Such leaf is mixed with leaf that was plucked continuously during the day. The situation is further complicated by poor state of tea roads, that are particularly difficult to manage during rainy seasons, which usually are also the peak production seasons (22). Plucked leaf can therefore last up to more than 30 hours before arriving at the factory.…”
Section: Introductionmentioning
confidence: 99%